KECERDASAN BUATAN SEBAGAI INVENTOR: STUDI KOMPARATIF KEPEMILIKAN DAN KEBIJAKAN PATEN DI INDONESIA DAN AMERIKA SERIKAT - Ruhtiani, Maya (J-LEE - Journal of Law, English, and Economics, 2025)
This study examines the status of artificial intelligence (AI) as an inventor within patent law systems and compares the regulation of patent ownership for AI-based inventions in the context of employee invention between Indonesia and the United States. The advancement of AI technology has enabled the creation of significant inventions without direct human intellectual input, raising legal issues regarding the recognition of inventors and ownership rights. This research employs a normative juridical method with statutory and comparative approaches to analyze two distinct legal systems: Indonesia’s civil law and the United States’ common law. Data were collected through literature review of relevant regulations, court decisions, and academic works on intellectual property and technology law. The findings reveal that both countries do not recognize AI as a legal inventor, but they adopt different approaches to ownership regulation. Indonesia provides explicit legal norms in Articles 12 and 15 of Law Number 13 of 2016 on Patents, while the United States relies on contractual agreements between parties. The novelty of this study lies in its integration of AI inventorship issues within the employee invention context, a topic that remains underexplored in existing scholarship. Therefore, regulatory reform is needed to address technological developments, alongside the formulation of clearer employment agreements to ensure legal certainty for all stakeholders.